2013
DOI: 10.3390/catal3020584
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases in Ionic Liquids—The Long Term Stability of Aspergillus sp. Cellulase

Abstract: It is a well known fact that some ionic liquids (ILs) have the potential to dissolve crystalline, water-insoluble cellulose that could be used as a source of glucose and subsequently derived molecules. Nevertheless, in the presence of high IL concentrations, cellulase activity and, even more so, cellulase stability are still challenging difficulties that need to be overcome. Therefore four fungal cellulase preparations were assayed in the presence of 30% (v/v) of five different ILs. Thereby the cellulase from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…was found to retain a remarkable activity in 30% ( among which was the cellulose-dissolving [BMIM]Cl earlier reported to be severely inactivating. 149 The other cellulases became almost completely inactivated under the corresponding conditions. Also the long term stability of this cellulase was found to be extraordinarily high in 60% (v/v) of IL.…”
Section: Enzymatic Hydrolysis Of Lignocellulosic Polysaccharides In Tmentioning
confidence: 99%
“…was found to retain a remarkable activity in 30% ( among which was the cellulose-dissolving [BMIM]Cl earlier reported to be severely inactivating. 149 The other cellulases became almost completely inactivated under the corresponding conditions. Also the long term stability of this cellulase was found to be extraordinarily high in 60% (v/v) of IL.…”
Section: Enzymatic Hydrolysis Of Lignocellulosic Polysaccharides In Tmentioning
confidence: 99%
“…The hyperthermophilic GH12 endoglucanase from Sulfolobus solfataricus could hydrolyse the dissolved microcrystalline cellulose (MCC) well even in an 80% (v/v) concentration of [EMIM]OAc at 90 C (Klose et al 2012). Cellulases and xylanases even from mesophilic microorganisms can show high activity and stability in ILs (Bose et al 2012;Ilmberger et al 2013;Hu et al 2016). These studies suggest that thermostability is not the sole factor in IL tolerance and other factors like halotolerance and surface charges contribute to resistance against the ILs (Pottk€ amper et al 2009;Ilmberger et al 2012;Nordwald and Kaar 2013;Trivedi et al 2013).…”
Section: Using Ionic Liquid-tolerant Cellulases and Xylanasesmentioning
confidence: 99%
“…Although many enzymes of other classes do not display their best activities in ionic liquids comprising chloride ions, a great number of cellulases seem to be particularly affected by [Cl] (Paljevac et al, 2006; Salvador et al, 2010; Ilmberger et al, 2013; Yoshimoto et al, 2013; Jaeger et al, 2015). For the highly positively surface-charged T. maritima celullase, which is also particularly enriched in α-helices, an investigative comparison between [C 4 C 1 Im] and [C 2 C 1 Im], in combination with [Cl] and [OAc], revealed that although conformational stability in low concentrations (0.2 M) of [C 4 C 1 Im][Cl] was extremely similar to the aqueous system with 10 mM phosphate buffer, a considerably decreased conformational stability in 0.2–0.5 M [C 4 C 1 Im][OAc] correlated with a considerably higher relative activity than for the other solvent systems, including the aqueous environment (Kudou et al, 2014).…”
Section: Enzymesmentioning
confidence: 99%